Fractal dynamics of heart rate variability for short term - Cardoso, Marco A.; Antonio, Ana Marcia; Abreu, Luiz Carlos de; Raimundo, Rodrigo Daminello; Fontes, Anne Michelli G.; Silva, Ariany Garcia da; Ogata, Cristiane Mayumi; Morini, Sarah Moreno; Sousa, Fernando Henrique; Amaral, Joice Anaize Tonon do; Nogueira, MArcela Leme; Cano, Amanda de Souza; et al. (My University, 2014)
The fractal analysis of heart rate variability (HRV) has been associated to the chaos theory. We evaluated the association of the fractal exponents of HRV with the time and frequency domain and geometric indices of HRV for short period. HRV was analyzed with a minimal number of 256 RR intervals in the time (SDNN-standard deviation of normal-to-normal R-R intervals, pNN50-percentage of adjacent RR intervals with a difference of duration greater than 50ms and RMSSD-root-mean square of differences between adjacent normal RR intervals in a time interval) and frequency (LF-low frequency, HF-high frequency and LF/HF ratio) domains. The geometric indexes were also analyzed (RRtri-triangular index, TINN-triangular interpolation of RR intervals and Poincaré plot) as well as short and long-term fractal exponents (alpha-1 and alpha-2) of the detrended fluctuation analysis (DFA). We observed strong correlation of the alpha-1 exponent with RMSSD, pNN50, SDNN/RMSSD, LF (nu), HF (nu), LF/HF ratio, SD1 and SD1/Sd2 ratio. In conclusion, we suggest that the alpha-1 exponent could be applied for HRV analysis with a minimal number of 256 RR intervals.